Contribution of Ultra-processed Food to the Daily Food Intake of HIV-positive and HIV-Negative Women during Pregnancy - Clarissa de Oliveira Agostini; Ester Zoche; Rafaela da Silveira Corrêa; Eunice Beatriz Martin Chaves; Helena von Eye Corleta; Vera Lúcia Bosa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To assess the daily dietary intake and energy contribution of ultraprocessed foods among women who are positive and negative for the human immunodeficiency virus (HIV) during pregnancy. Methods This case-control study included 77 HIV-positive and 79 HIV-negative puerperal women between 2015 and 2016. The socioeconomic and maternal demographic data were assessed, and a food frequency questionnaire (FFQ) adapted for pregnant women was applied. The Fisher exact test and the Mann-Whitney test were applied to detect differences between the groups. Linear regression was used to assess the associations between the intake of ultra-processed food and energy, macro- and micronutrients, with values of p < 0.05 considered significant. Results The HIV-positive group was older (p< 0.001) and had lower income (p= 0.016) and level of schooling (p< 0.001) than the HIV-negative group. Both groups presented similar average food intake: 4,082.99 Kcal/day and 4,369.24 Kcal/day for the HIV-positive and HIV-negative women respectively (p= 0.258).The HIV-positive group consumed less protein (p= 0.048), carbohydrates (p= 0.028) and calcium(p= 0.001), andmore total fats (p= 0.003). Ultra-processed foods accounted for 39.80% and 40.10% of the HIV-positive and HIV-negative groups' caloric intake respectively (p= 0.893). The intake of these foods was associated with a higher consumption of carbohydrates (p < 0.001), trans fat (p= 0.013) and sodium (p< 0.001), as well as lower protein (p < 0.001) and fiber intake (p= 0.022). Conclusion These findings demonstrate that the energy consumption and ultraprocessed food intake were similar in both groups, which reinforces the trend toward a high intake of ultra-processed food in the general population. The intake of ultraprocessed food was positively associated with the consumption of carbohydrates, trans fat and sodium, and negatively associated with the consumption of protein and fiber.